Crystal structures of three bicyclic carbohydrate derivatives - Schilde, Uwe (Acta Crystallogr E Crystallogr Commun, 2016)
The title compounds, [(1R,3R,4R,5R,6S)-4,5-bis(acetyloxy)-7-oxo-2-oxabicyclo[4.2.0]octan-3-yl]methyl acetate, C(14)H(18)O(8), (I), [(1S,4R,5S,6R)-5-acetyloxy-7-hydroxyimino-2-oxobicyclo[4.2.0]octan-4-yl acetate, C(11)H(15)NO(6), (II), and [(3aR,5R,6R,7R,7aS)-6,7-bis(acetyloxy)-2-oxooctahydropyrano[3,2-b]pyrrol-5-yl]methyl acetate, C(14)H(19)NO(8), (III), are stable bicyclic carbohydrate derivatives. They can easily be synthesized in a few steps from commercially available glycals. As a result of the ring strain from the four-membered rings in (I) and (II), the conformations of the carbohydrates deviate strongly from the ideal chair form. Compound (II) occurs in the boat form. In the five-membered lactam (III), on the other hand, the carbohydrate adopts an almost ideal chair conformation. As a result of the distortion of the sugar rings, the configurations of the three bicyclic carbohydrate derivatives could not be determined from their NMR coupling constants. From our three crystal structure determinations, we were able to establish for the first time the absolute configurations of all new stereocenters of the carbohydrate rings.